THE ROLE OF THE SPEECH THERAPIST IN THE TREATMENT OF HEARING IMPAIRED CHILDREN - THE IMPORTANCE OF EARLY INTERVENTION: - Ilić Savić, Ivana; Petrović-Lazić, Mirjana (HEALTH CARE, 2025)
The aim of this review is to present the relationship between early intervention in speech rehabilitation and the success of speech therapists in speech habilitation in hearing impaired children. Proper hearing is one of the most important prerequisites for the proper development of speech, because speech is learned by listening. It is necessary for parents to turn to a speech therapist for help if the child's vocalization is absent or stops suddenly, if he does not respond to sounds from the environment, if he does not turn to the call of the interlocutor who is not in his field of vision, if he does not respond to simple verbal commands, if during the conversation he focuses strongly on the face of another person, if he approaches the sound source or tries to amplify the sound, as well as if there is a lack of socialization with to family members. Early treatment of children with hearing impairment involves a series of stimulating activities aimed at improving the child's development, especially the development of speech and auditory attention. The modern approach to speech and language habilitation places great emphasis on the development of verbal communication, which is crucial for the common life of children with hearing impairments and hearing children, especially in the period when children want to socialize with their peers. Early intervention is critical because a child's brain develops faster from conception to age three than at any time later in life. Children who are involved in the process of installing a cochlear implant before the age of one have a greater chance of achieving their full potential compared to children who are implanted around the age of three.
Keywords: early intervention, speech habilitation, hearing impaired children